A dynamic model of etiology in sport injury: the recursive nature of risk and causation - Meeuwisse, W. H.; Tyreman, H.; Hagel, B.; Emery, C. (Clinical Journal of Sport Medicine, 2007)
The purpose of this manuscript is to outline a new model representing a dynamic approach that incorporates the consequences of repeated participation in sport, both with and without injury. This model builds on the previous work, while emphasizing the fact that adaptations occur within the context of sport (both in the presence and absence of injury) that alter risk and affect etiology in a dynamic, recursive fashion. Regardless of the type of injury, it is often preceded by a chain of shifting circumstances that, when they come together, constitute sufficient cause to result in an injury. If we are to truly understand the etiology of injury and target appropriate prevention strategies, we must look beyond the initial set of risk factors that are thought to precede an injury and take into consideration how those risk factors may have changed through preceding cycles of participation, whether associated with prior injury or not. This model considers the implications of repeated exposure, whether such exposure produces adaptation, maladaptation, injury or complete/incomplete recovery from injury. When feasible, future studies on sport injury prevention should adopt a methodology and analysis strategy that takes the cyclic nature of changing risk factors into account to create a dynamic, recursive picture of etiology.